Strength Matching Method for Improving the Gear Transmission Life - Tan Wei; Yun Hongyuan (Jixie chuandong)
The life of transmission element is not equal often occurs in the standard design of the transmission pair,this problem can be effectively solved through the strength matching of transmission element. Starting from the meshing principle,by changing the standard of usual parameters,which makes the design of worm pair can meet the requirements of transmission ratio and strength,but also reflects the structure compact,while the meshing strength matching of transmission parts is realized. The two parameter correction schemes: the method of variable modulus and pressure angle and variable,and the method of single variable tooth thickness are mainly studied. The feasibility and effectiveness of the two methods are proved by the practice.